Expansão da educação tecnológica em São Paulo entre 2004 e 2018: como pensam os professores - Borges, Rafael dos Santos (2019)
The present research deals with the expansion of Professional Technological Higher Education in Sao Paulo State. The first part elicits the research question: the technological higher education course and its formation. As a second aim, we can contribute to a reflection around the universality of technological higher education course, thus we might follow and unveil dilemmas that are part of its recent expansion and its role in a historical context and an international economy. Fatec Rio Preto, which belongs to Centro Paula Souza autarchy from State government was elected as our field research. Our research questions are: the nature of Technological Education which higher education and professional education at the same time is. This research highlights the expansion of technological higher education in Sao Paulo State and pointed out changes made by the PSDB (The Brazilian Social Democracy Party) government among 2014 and 2018. It was considered the historical expansion context of Professional Technological Higher Education as well as the Workers’ Party government at the federal level. Our work also copes with the pressions of international order in an international policy and economy to understand the phenomenon. It was also reflected about Information Technologies and the changes in the productive and economics forces in order to establish the connection between changes and ideology among workers who have received their formation based on technological education curriculum. A literature review gave us a better understanding around the terms “competent discourse”; “meritocracy” and “technocracy”. Theory studies are based on Sacristán and Santomé where themes like curriculum and conflict were discussed; Young is an interpretative alternative to this conflict, therefore concepts such as “knowledge of the powerful people” and “powerful knowledge”. Moreover “communicative action”, as defined by Habermas was used to understand the curriculum of Professional Technological Higher Education. Finally the concept of technology by Álvaro Vieira Pinto. The research field was applied to forty-seven university professors at Fatec Rio Preto. The survey questionnaire aimed to understanding how this public think about the curriculum. Besides six university professors were interviewed in order to help us to reflect on Fatec Rio Preto curriculum. Thus, it allows us to contribute to a more general reflection about the Professional Technological Higher Education. As a result, it was possible to comprehend how university professors see the curriculum and the technological formation